2019
DOI: 10.1038/s41556-019-0418-y
|View full text |Cite
|
Sign up to set email alerts
|

Haematopoietic stem cells in perisinusoidal niches are protected from ageing

Abstract: With ageing, intrinsic haematopoietic stem cell (HSC) activity decreases, resulting in impaired tissue homeostasis, reduced engraftment following transplantation and increased susceptibility to diseases. However, whether ageing also affects the HSC niche, and thereby impairs its capacity to support HSC function, is still widely debated. Here, by using in-vivo long-term labelretention assays we demonstrate that aged label-retaining HSCs, which are, in old mice, the most quiescent HSC subpopulation with the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(116 citation statements)
references
References 79 publications
3
112
0
1
Order By: Relevance
“…in controlling changes in cell polarity in other cell types have been previously reported 19,22,37 . A polar phenotype of Cdc42 in HSCs is associated with a strong regenerative capacity, similar to what is here reported for HFSCs 38 . Cdc42 itself is part of the cytoplasmic protein polarity complex (Par6-Cdc42-aPKC) that is known to regulate the activity of PKC to maintain apico-basal polarity in epithelial cells 39,40 .…”
Section: Elevated Levels Of Wnt5a and Increased Cdc42 Activity Alter supporting
confidence: 87%
“…in controlling changes in cell polarity in other cell types have been previously reported 19,22,37 . A polar phenotype of Cdc42 in HSCs is associated with a strong regenerative capacity, similar to what is here reported for HFSCs 38 . Cdc42 itself is part of the cytoplasmic protein polarity complex (Par6-Cdc42-aPKC) that is known to regulate the activity of PKC to maintain apico-basal polarity in epithelial cells 39,40 .…”
Section: Elevated Levels Of Wnt5a and Increased Cdc42 Activity Alter supporting
confidence: 87%
“…The LR-HSCs (≤ 4 divisions) in old mice contain only fHSCs which still preserve multipotency (with a myeloid bias) and self-renewal potential, whereas the H2B-GFP − non-LR-HSCs (> 4 divisions) represent functionally defective HSCs, intermediate HSCs and lineage-restricted progenitors. Thus, non-LR-HSCs have minimal self-renewal and restricted regenerative capacity [ 81 , 82 ]. Szade’s lab found that Neo1 is a better marker for separating My-bi HSCs from Bala-HSCs.…”
Section: Increase In Lineage-biased Hscs and Functionally Defective Hmentioning
confidence: 99%
“…The age-related reduction in endosteal/arteriolar niches is associated with the downregulation of Notch ligands Dll1 and Dll4 in type-H ECs, suggesting aging-related impairment of Notch signaling in the arteriolar niche [ 236 , 278 , 279 ]. In addition, due to the lack of recovery of expression of the endothelial Notch ligand Jag2 after chemotherapy in old sinusoid ECs, such drug treatment causes long-term hematopoietic disruption in the elderly owing to the attenuated recovery of sinusoidal niches [ 81 , 278 ]. The results of these studies suggest that altered Notch signaling critically contributes to the aging-related defects of both endosteal/arteriolar and sinusoid niches of HSCs [ 81 ] (Fig.…”
Section: Age-related Hsc Niche Changesmentioning
confidence: 99%
“…As well, it is highly likely that cell extrinsic factors (exogenous stressors and alterations of the bone marrow microenvironment) and alterations in cell polarity [14] are major contributors to the trajectory of disease development. Recently, many reports have been dealing with the alterations in hematopoietic stem cell polarity and in the aged bone marrow microenvironment offering new insights into these topics [15][16][17].…”
Section: Aml Initiating Eventsmentioning
confidence: 99%
“…In addition to cell-intrinsic forces driving the age-associated CH, such as acquisition of driver mutations, the role of the aged microenvironment in promoting this potentially leukemogenic clonal expansion has been suggested [82]. Indeed, some recent reports highlighted profound alterations in the BM microenvironment on aging which might play important roles in disease progression, or it might be critical to tailor the chemotherapeutic approach for the elderly [16,17,83,84]. Interestingly, the three genes most frequently found to be involved in CH in healthy aged individuals are DNMT3A, TET2, and ASXL1.…”
Section: Clonal Hematopoiesis In Elderlymentioning
confidence: 99%